Um modelo de software colaborativo com suporte a troca de informações entre equipes médicas plantonistas - Marques, Vinícius Tocantins (Universidade do Vale do Rio dos Sinos, 2016)
Technological applications used in medical emergencies is one of the greatest support tools for attending physicians teams in this new century. The Ubiquitous Computing and the Situation Awareness are evolving elements for computer applications in hospitals. Specifically, the application that is able to correlate data from heterogeneous networks to improve the success of health care, produces a wide collaboration network. Beside that, the patient can benefit from various views of a wide range of medical specialists, all in favor of their welfare. Overall the results of researches are works that address the topics of different forms. One of the articles did not apply the concepts of ubiquitous computing in order to minimally interfere with the day-to-day medical team. In this context, this paper proposes the development of a collaborative model that supports the exchange of information between physicians medical teams using the Situation Awareness. The model aims to use ubiquitous computing resources to improve the inclusion of relevant data in the application, as well as optimize the data output on mobile devices. As scientific contribution, the proposed model employs computational inferences by using Situation Awareness in order to improve medical decision making and support collaboration between medical teams. The proposed model had two evaluations, one through case study and the other regarding the usability of the model. Evaluations show that the Doctor Collab reached an average of 86.9% acceptance using the Technical Architecture Modelling model to check the assent of application to the attending physicians. In this way it way be indicated that the proposed model is consistent with the identified assumptions.
Keywords: Ciência de situação; Redes colaborativas; Emergência médica; Cuidados ubíquos; Ontologia; Computação baseada em atividades; Situation awareness; Collaborative computing; Medical emergency; Ubiquitous computing; Ontology; Activity-based computing; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação